Histomorphological Spectrum of Ovarian Masses in a Tertiary Centre of Eastern Nepal - Shrestha, Oshan; Baral, Reetu; Shrestha, Shipra (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To analyze the trends of ovarian masses in a tertiary centre in eastern Nepal. Methods: This was a retrospective cross sectional study conducted in Department of Pathology at Nobel Medical College and teaching hospital, Biratnagar, Nepal. Database of two years from April 2019 to April 2021 was searched. Gross and microscopic findings of cases including demographic details of patients with ovarian mass were analyzed and presented by descriptive parameters. Results: Out of 127 cases of ovarian masses studied, 95 (74.8%) were neoplastic. The common types were Germ cell tumors were (47; 37%), epithelial tumors (43; 33.9%) and endometriotic cyst (23; 18.1%). Mean age was 38.1 (range: 17-77) years in benign, 47.1 (30 – 70) years in malignant and 36.9 (21-53) years in non-neoplastic tumors; 11 cases were malignant and 63.6% were solid; and 23.8% of serous tumors were bilateral. Conclusions: Benign neoplastic lesions were the most common lesions and presented earlier than borderline and malignant lesions. Endometriotic cysts comprised the most common non- neoplastic lesions. The non-neoplastic lesions were predominantly cystic and the malignant lesions were predominantly solid. Most of the benign lesions were solid-cystic. Most mucinous tumors and all the sex-cord stromal tumors were unilateral while the seromucinous tumor and a significant number of serous tumors were bilateral.